Pengaruh Periklanan, Kualitas Pelayanan, Jaminan Rasa Aman Dan Hubungan Masyarakat Terhadap Minat Menabung Nasabah Bmt Assyafiiyah Di Kota Gajah Lampung Tengah - Yulianti, Indri; Dupri, Muhammad Demsi (Universitas Muhammadiyah Metro, 2021)
This study aims to determine the effect of advertising, service quality, guarantee of security and public relations on the saving interest of customers of BMT Assyafiiyah in Gajah City, Central Lampung. Data obtained from the questionnaire. The data analysis of this research was carried out using the Instrument Requirements Test, the analysis requirements testing for regression (Cross Section) and hypothesis testing. The results of this study indicate that advertising, quality of service, assurance of security and public relations together have an effect on customers' interest in saving at BMT Assyafiiyah Gajah City, Central Lampung. Keywords: Advertising, Service Quality, Security Assurance, Public Relations, Interest in Saving